Determination of Ascorbic Acid in Common Fruits, Herbal Tea by Using Cuprac and Cerac Methods - Karasakal, Ayca; Yalcin Gurkan, Yelda (Asian Journal of Chemistry, 2012)
The method used to determine the ascorbic acid (Vitamin C) is based on the oxidation of ascorbic acid to dehydroascorbic acid with the cupric ion reducing antioxidant capacity (CUPRAC) and ceric-reducing antioxidant capacity (CERAC) reagent of total antioxidant capacity assay. The antioxidant capacity indicates the degree of protection of a certain organism against oxidative damage provoked by reactive oxygen and nitrogen species. These methods were applied to a number of commercial fruits and blackberry herbal tea. The findings of cupric ion reducing antioxidant capacity method are statistically compared to those of the ceric-reducing antioxidant capacity method, which is a relatively new one. In addition to this, we were also investigated the kinetic degradation of the ascorbic acid in a certain type of fruit juice.